P Perancangan Buku Explainer Digital Sebagai Media Edukasi Untuk Anak Mengenai Bahaya Pengaruh Media Sosial Berlebihan - Wasesa, Anisa; Anwar, Ahmad Khoirul (JURNAL KEMADHA, 2025)
Social media is a platform or application that facilitates online interaction. Social media is found in everyday life, with platforms like YouTube, TikTok, Twitter, and Instagram available. Social media has become a popular entertainment platform for teenagers, parents, and children, offering numerous benefits in providing a variety of information and content quickly. However, social media also has negative impacts, especially when children are influenced by it. Excessive scrolling can lead to decreased thinking skills due to excessive consumption of digital content. The goal of this design is to create a book that can serve as an educational medium for children about the dangers of social media influence. The creation of this digital explainer book applies the design thinking method based on the Institute of Design at Stanford. The stages in design thinking are: empathize, define, ideate, prototype, and test. These elements summarize the design foundation. The result of this design is a prototype. Therefore, this digital explainer book can be a medium for providing understanding aimed at educating children about the wise use of social media.